(untitled) (Praxis Educativa, 2023)
The processes of teacher training are frameworks that express a range of senses and meanings that show the imaginaries and self-representations that both trainers and students generate from the relationships they establish with themselves, with others and with the context in which they interact. Due to this, the present article was aimed at analyzing the teaching practices implemented by teacher educators, from an analytical approach of their autoethnographic expressions that would allow to account for the asymmetrical power relations that exist in an educational, social and cultural environment. The research was developed in a normal school in the state of Oaxaca, Mexico, from an interpretative perspective, based on the theoretical and methodological references of the contact zone. The results show the scope made by the trainers according to the personal and social constructs that they imprint on their discourses and pedagogical practices.